Pengaruh Penggunaan Celebrity Endorser Terhadap Brand Attitude The Body Shop Indonesia - Patricia Patricia; Rodhiah Rodhiah (Jurnal Manajerial Dan Kewirausahaan, 2021)
The purpose of this research is to examine the effects of attitude towards the celebrity, celebrity—brand fit, celebrity expertise, and celebrity motive on brand attitude and how attitude towards the endorsement mediates the effects of attitude towards the celebrity, celebrity—brand fit, celebrity expertise, and celebrity motive on brand attitude. The population of this study is consumers of The Body Shop in Jakarta who acknowledge Jerinx. This research uses a descriptive approach. Sampling was done using a purposive sampling method. In total there were 100 respondents who participated. Data were collected using an online questionnaire, Google Form. The analysis used is structural equation modeling (SEM) with SmartPLS as a tool for analyzing data. The result of this study indicate that celebrity motive has a positive and significant effect towards brand attitude, while attitude towards the celebrity, celebrity—brand fit, and celebrity expertise have positive and not significant effects towards brand attitude. Attitude towards the endorsement is a positive and significant mediator of attitude towards the celebrity, celebrity—brand fit, celebrity expertise, and celebrity motive towards brand attitude. Furthermore, this research can be used as new insights for brands on advertising their products using celebrity endorsement, how and what to consider for choosing the right celebrity endorser.Tujuan dari penelitian ini adalah untuk menguji pengaruh attitude towards the celebrity, celebrity—brand fit, celebrity expertise, dan celebrity motive terhadap brand attitude dan attitude towards the endorsement memediasi pengaruh attitude towards the celebrity, celebrity—brand fit, celebrity expertise, and celebrity motive terhadap brand attitude. Populasi penelitian ini adalah konsumen The Body Shop di Jakarta yang mengetahui sosok Jerinx. Penelitian ini menggunakan pendekatan deskriptif. Pengambilan sampel dilakukan dengan menggunakan teknik pendekatan purposive sampling. Secara total terdapat 100 responden yang berpartisipasi. Data dikoleksi menggunakan kuisioner online, Google Form. Analisis yang digunakan adalah structural equation modeling (SEM) dengan menggunakan SmartPLS sebagai alat untuk menganalisis data. Hasil dari penelitian ini menunjukkan bahwa celebrity motive memiliki pengaruh positif dan signifikan terhadap brand attitude, sementara attitude towards the celebrity, celebrity—brand fit, dan celebrity expertise memiliki pengaruh positif dan tidak signifikan terhadap brand attitude. Attitude towards the endorsement merupakan mediator positif dan signifikan dari attitude towards the celebrity, celebrity—brand fit, celebrity expertise, and celebrity motive pada brand attitude. Selanjutnya, penelitian ini dapat digunakan sebagai wawasan bagi perusahaan dalam periklanan dengan menggunakan strategi celebrity endorsement, bagaimana dan apa yang perlu dipertimbangkan dalam memilih celebrity endorser.